Dietary seaweed extract mitigates oxidative stress in Nile tilapia by modulating inflammatory response and gut microbiota - Siddik, Muhammad A. B.; Francis, Prue; Foysal, Md Javed; Francis, David S. (Frontiers in Immunology, 2024)
IntroductionExtreme water temperature affects the well-being of all aquatic animals, including fish. Higher temperatures can lead to the generation of reactive oxygen species (ROS), which can induce oxidative stress and negatively impact fish health and well-being. This study investigated the protective effects of seaweed extract on growth, antioxidant status, inflammatory responses, and gut microbiota to gain a better understanding of the acclimatization ability of Nile tilapia, Oreochromis niloticus in response to oxidative stress caused by high water temperatures.MethodsRed-seaweed, Gracilaria tenuistipitata rich in polyphenols (i.e., total phenolics and flavonoids content) was considered for the preparation of the Gracilaria extract (GE) for the study. Nile tilapia were fed the GE supplemented diet along with a control diet for 42 days, followed by 14 days of temperature ramping at a rate of 1°C every two days to the desired target (35°C) and 14 days of holding at 32°C for acclimatation.ResultsNile tilapia fed the GE had a significantly higher growth performance attributed to increased muscle fiber size compared to control (p < 0.05) after the 70 days of feeding trial. Fish fed the GE diet also showed a significantly lower lipid peroxidation by decreased malondialdehyde level when compared to control (p < 0.05). Furthermore, GE diet exhibited increased red blood cell counts with the decreased number of cellular and nuclear abnormalities. The gene expression of tight junction (i.e., occludin, claudin1, ZO-1) and nrf2 (antioxidant biomarker) were upregulated, while hsp70 (related to stress response) was downregulated in fish fed the GE diet. Additionally, GE supplementation led to an increase in bacterial diversity and the abundance of phylum Firmicutes, order Lactobacillales, and genera Sphingobacterium and Prevotella in the distal gut of Nile tilapia, which are mostly considered as beneficial for fish.ConclusionThe findings suggest that GE has the potential to be used as a dietary supplement to improve health, particularly as a stress-resistant supplement in the diet for Nile tilapia. This study may help make more informed decisions for tailoring the nutrient requirements of fish in the face of climate warming.